221 IDENTIFICATION OF NOVEL FACTORS THAT REGULATE PITUITARY TUMORIGENESIS. (1st January 2005) - McDermott, D. S.; Lotts, M. M.; Ertel, J. R.; Xu, M.; Li, H. Y.; Lillehei, K. O.; DeMasters, B. K.; Nielsen-Preiss, S. M.; Pawlowski, J. E.; Wierman, M. E.
Abstract : Gonadotropinomas that make α, LHβ and/or FSHβ glycoprotein hormone subunits are the most prevalent type of pituitary macroadenoma. These tumors present a diagnostic challenge, as they are rarely associated with a characteristic clinical hypersecretory syndrome and thus difficult to recognize until large enough to cause mass effects. Mechanisms underlying the pathogenesis of gonadotropinomas have not been identified. Common oncogene mutations involved in other human cancers, such as Ras and Rb, are not involved in pituitary tumor formation. The aims of the current study were to elucidate molecular events responsible for the development of gonadotropinomas. We compared gene expression profiles between six normal human pituitaries and five glycoprotein-secreting tumors by cDNA microarray analysis. Pairwise comparisons of normal pituitaries and gonadotropinomas demonstrated consistent, greater than two-fold increased expression in 671 genes and decreased expression in 878 genes. Gene Ontology Database analysis was used to categorize differentially expressed genes into classes that may affect tumorigenic or cell proliferative properties. Relative to tumor versus normal, the following data were obtained: transcription factors (184 up/165 down), cell cycle regulation (104 up/62 down), apoptosis regulation (68 up/50 down), cancer genes (72 up/55 down), and signal transduction (158 up/240 down). Candidate genes were then selected based on the magnitude and consistency of change. RT-PCR was performed to confirm array-based results of differential expression in candidate genes. Deleted in Bladder Cancer Chromosome Region 1-Like (DBCCR1-L) is an attractive candidate as it was completely absent in all normal pituitary samples, but expressed in all tumor samples. DBCCR1-L is a novel gene. Its homologue, DBCCR1, is involved in G1 cell cycle transition and colon, breast, esophageal, ovarian, and bladder cancer. Investigation is underway to evaluate the consequences of DBCCR1-L knockdown and overexpression in pituitary cell lines and its effects on cell cycle progression. Our results demonstrate the differential expression of many genes, including DBCCR1-L, which may be involved in pituitary tumorigenesis. Future studies on candidate genes identified in this analysis may lead to the identification of tumor markers to detect, prognostically evaluate, and eventually medically treat gonadotropinomas. Sponsored by VA Merit to MEW and NIH and UCHSC Cancer Center Fellowships to DSM and MML